Tumor necrosis factor receptor‐associated factor 6 participates in early brain injury after subarachnoid hemorrhage in rats through inhibiting autophagy and promoting oxidative stress. Issue 3 (20th June 2017) - Dou, Yang; Shen, Haitao; Feng, Dongxia; Li, Haiying; Tian, Xiaodi; Zhang, Jian; Wang, Zhong; Chen, Gang
Abstract: Tumor necrosis factor receptor‐associated factor 6 (TRAF6) is a member of the TRAF family and an important multifunctional intracellular adaptin of the tumor necrosis factor superfamily and toll/IL‐1 receptor (TIR) superfamily. TRAF6 has been studied in several central nervous system diseases, including ischemic stroke, traumatic brain injury, and neurodegenerative diseases, but its role in subarachnoid hemorrhage (SAH) has not been fully illustrated. This study was designed to explore changes of expression level and potential roles and mechanisms of TRAF6 in early brain injury (EBI) after SAH using a Sprague–Dawley rat model of SAH induced in 0.3 mL non‐heparinized autologous arterial blood injected into the pre‐chiasmatic cistern. First, compared with the sham group, we found that the expression levels of TRAF6 increased gradually and peaked at 24 h after SAH. Second, the results showed that application of TRAF6 over‐expression plasmid and genetic silencing siRNA could increase or decrease expression of TRAF6, respectively, and severely exacerbate or relieve EBI after SAH, including neuronal death, brain edema, and blood–brain barrier injury. Meanwhile, the levels of autophagy and oxidative stress were reduced and increased separately. Finally, GFP‐TRAF6‐C70A, which is a TRAF6 mutant that lacks E3 ubiquitin ligase activity, was used to explore the mechanism of TRAF6 in SAH, and the results showed that EBI and oxidative stress were reduced, but the levels of autophagy were increased under this condition. Collectively, these results indicated that TRAF6 affected the degree of EBI after SAH by inhibiting autophagy and promoting oxidative stress. Abstract : Tumor necrosis factor receptor‐associated factor 6 (TRAF6) has been studied in several central nervous system (CNS) diseases but its role in subarachnoid hemorrhage (SAH) has not been fully illustrated. We show that TRAF6 is activated to ubiquitin upon SAH through the Toll‐like receptor 4/Myeloid differentiation primary response gene 88 (TLR4/MyD88) pathway. Then, it translocates to mitochondria and promotes Evolutionarily conserved signaling intermediate in toll pathway (ECSIT) ubiquitination, thus increasing production of reactive oxygen species (ROS). In addition, the ubiquitination of TRAF6 can increase degradation of Unc‐51 Like Autophagy Activating Kinase 1 (ULK1) and reduce its phosphorylation, thereby inhibiting autophagy. These processes can exacerbate early brain injury (EBI) after SAH.